Sistem Aplikasi Pencarian Lokasi Parkir Terdekat Menggunakan Location Based Service Berbasis Android - Sri Nurhayati; Egi Nur Ilmi (Komputika : Jurnal Sistem Komputer, 2017)
The purpose of this research is to make the closest parking search application so that it can make it easier for parkers to find the nearest and empty parking lot. Parking activities that are carried out carelessly in places that are not intended will lead to traffic congestion. This happened because it was caused by the inability of vehicle users to find out about the parking places or because the existing parking lot was full. The object of this study is the location of parking lots in the city of Bandung. Analysis of the application system made in this study uses an object-based programming approach with Unified Modeling Language (UML) tools. The Location Based Service (LBS) method is used to analyze the search for the nearest parking location. Based on the results of application testing, the application can be implemented properly on android devices and can help parking users in finding empty parking lots and the closest to the user. Keywords – Parking, Location Based Service (LBS), Unified Modeling Language (UML), Object-Based Programming